2022
DOI: 10.1088/1742-6596/2265/2/022012
|View full text |Cite
|
Sign up to set email alerts
|

Wind farm optimization with multiple hub heights using gradient-based methods

Abstract: Optimization of the Levelized Cost of Energy (LCoE) in wind farms helps ensure profitability and competitiveness of the project. Recent work has explored driving down LCoE by allowing multiple wind turbines in a single wind farm - with different hub heights, rotor diameters, and rated powers. In this work, we performed optimization of the Lillgrund wind farm with continuously varying hub-heights to mitigate wake interference, improve annual energy production (AEP) and reduce LCoE. The optimization converged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Furthermore, other features can be coupled to the surrogate to increase its capabilities, for instance, foundation structures and wind farm geometrical archetypes other than rectangular. Hub heights can also be considered in future works, as its importance has been highlighted in previous works (for instance, [23]).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, other features can be coupled to the surrogate to increase its capabilities, for instance, foundation structures and wind farm geometrical archetypes other than rectangular. Hub heights can also be considered in future works, as its importance has been highlighted in previous works (for instance, [23]).…”
Section: Resultsmentioning
confidence: 99%
“…All the simulations were performed in PyWake [12,13] and TOPFARM [14], an open-source tool developed by DTU Wind and that has been used in previous works in the literature [15,16,17,18,19]. The case-study considered in this work is the Borselle wind farm, which has 74 wind turbines with 10MW each.…”
Section: Optimization and Case Studymentioning
confidence: 99%
“…For the AEP calculation and the wake modeling involved in the simulations, TOPFARM relies in PyWake (Pedersen et al, 2019), another DTU open source Python library that offers fast AEP evaluation from a range of engineering wake models. Recent works using TOPFARM (Ciavarra et al, 2022;Riva et al, 2020), and PyWake (Rodrigues et al, 2022;Fischereit et al, 2021;Forsting et al, 2021;Pedersen et al, 2021;Quick et al, 2022) can be found in the literature.…”
mentioning
confidence: 99%